2015
DOI: 10.2741/4363
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan-kynurenine pathway is dysregulated in inflammation and immune activation

Abstract: The kynurenine (Kyn) pathway is the major route for tryptophan (Trp) metabolism, and it contributes to several fundamental biological processes. Trp is constitutively oxidized by tryptophan 2, 3-dioxygenase in liver cells. In other cell types, it is catalyzed by an alternative inducible indoleamine-pyrrole 2, 3-dioxygenase (IDO) under certain pathophysiological conditions, which consequently increases the formation of Kyn metabolites. IDO is up-regulated in response to inflammatory conditions as a novel marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(70 citation statements)
references
References 213 publications
(335 reference statements)
2
67
0
Order By: Relevance
“…To identify Kyn pathway catabolites that upregulate MMP2, the expression and activity of MMP2 were detected in HASMCs incubated with major exogenous metabolites 6, 37 of Trp degradation. A dramatic increase in MMP2 expression and activity was observed with 3-HAA, 3841 but not with Kyn, 10 3-HK, 10 kynurenic acid (KA), 42 AA, 43 xanthurenic acid (XA), 44 or quinolinic acid (QA) 45 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify Kyn pathway catabolites that upregulate MMP2, the expression and activity of MMP2 were detected in HASMCs incubated with major exogenous metabolites 6, 37 of Trp degradation. A dramatic increase in MMP2 expression and activity was observed with 3-HAA, 3841 but not with Kyn, 10 3-HK, 10 kynurenic acid (KA), 42 AA, 43 xanthurenic acid (XA), 44 or quinolinic acid (QA) 45 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In other cell types, Trp is catalyzed by an alternative inducible indoleamine-pyrrole 2,3-dioxygenase (IDO) under certain pathophysiological conditions. 6 The first stable intermediate from the Kyn pathway is Kyn. Subsequently, in eukaryotes, kynureninase (KNU) directly catalyzes the hydrolysis of Kyn or 3-hydroxykynurenine (3-HK) to form anthranilic acid (AA) or 3-hydroxyanthranilic acid (3-HAA), respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the multifaceted contribution of the kynurenine pathway in fundamental biological processes, impacting on inflammation, oxidative stress, and endothelial function, current literature suggests an involvement of kynurenine in both acute and chronic kidney disease [18, 28]. Previous studies have demonstrated that metabolites of the kynurenine pathway are elevated in CKD animal models as well as in CKD patients [21, 29], and kynurenine metabolites were shown to increase parallely to decreasing renal function [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Catabolites in the Kyn pathway of Trp catabolism are important for regulating the immune system and inflammation 10, 11. Emerging evidence also indicates that these catabolites play significant roles in cardiovascular pathophysiology 12, 13, 14…”
Section: Introductionmentioning
confidence: 99%